Reconciling state promises and practices: Constitutional promises and discrimination against religious minorities. (September 2021) - Finke, Roger; Mataic, Dane R
Research on religious freedom has found a vast chasm between constitutional promises and state practices, with constitutional promises being a poor predictor of the state's support of religious freedom. This research changes the focus from religious freedom to religious equality. We propose that constitutional promises of religious equality will be associated with less discrimination against minority religions and we explore the relationships governance and the promises of religious equality hold with religious discrimination. We find that promises of religious equality are associated with less discrimination. When exploring the interactions between promises of equality and our governance measures, we find constitutional promises of religious equality largely erase the differences in religious discrimination between countries with and without free elections and an independent judiciary. Yet, the reduced discrimination against minority religions does not suggest that the state removes restrictions on minority religions, only that they are equal with other religions.